2018
DOI: 10.3390/catal8040147
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Light-Driven Production of Hydrogen Peroxide by Anchoring Au onto C3N4 Catalysts

Abstract: Light-driven production of hydrogen peroxide (H 2 O 2 ) is a green and sustainable way to achieve solar-to-chemical energy conversion. During such a conversion, both the high activity and the stability of catalysts were critical. We prepared an Au-supported C 3 N 4 catalyst-i.e., Au/C 3 N 4 -500(N 2 )-by strongly anchoring Au nanoparticles (~5 nm) onto a C 3 N 4 matrix-which simultaneously enhanced the activity towards the photosynthesis of H 2 O 2 and the stability when it was reused. The yield of H 2 O 2 rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 49 publications
0
19
0
1
Order By: Relevance
“…[44] However,t wo recent studies found that Au NPs could be outstanding cocatalysts to improve the photocatalytic activity of g-C 3 N 4 for the synthesis of H 2 O 2 . [60] In one study reported by Chang et al, [60a] ac arbon-layer-stabilized method was adopted to load Au nanoparticles onto the C 3 N 4 matrix. They ield of H 2 O 2 with the fabricated Au/g-C 3 N 4 photocatalyst reached 1320 mmol L À1 after irradiation with light for 240 min;t his yield is 2.3-times higher than that of the pristine g-C 3 N 4 .Inthe other study,Zuo et al [60b] observed asimilar improvement in the production of H 2 O 2 production with aA u/C 3 N 4 photocatalyst.…”
Section: Loading Of Noble Metal Nanoparticlesmentioning
confidence: 99%
“…[44] However,t wo recent studies found that Au NPs could be outstanding cocatalysts to improve the photocatalytic activity of g-C 3 N 4 for the synthesis of H 2 O 2 . [60] In one study reported by Chang et al, [60a] ac arbon-layer-stabilized method was adopted to load Au nanoparticles onto the C 3 N 4 matrix. They ield of H 2 O 2 with the fabricated Au/g-C 3 N 4 photocatalyst reached 1320 mmol L À1 after irradiation with light for 240 min;t his yield is 2.3-times higher than that of the pristine g-C 3 N 4 .Inthe other study,Zuo et al [60b] observed asimilar improvement in the production of H 2 O 2 production with aA u/C 3 N 4 photocatalyst.…”
Section: Loading Of Noble Metal Nanoparticlesmentioning
confidence: 99%
“…For instance, loading Au nanoparticles on the surface of g-C 3 N 4 resulted in highly efficient and stable H 2 O 2 production because of the favorable two-electron ORR and the inert nature for catalyzing the decomposition of the produced H 2 O 2 over the hybrid catalyst. 144,145 As a noble-metalfree co-catalyst, CoP has also been loaded on the surface of g-C 3 N 4 to improve the photocatalytic H 2 O 2 production efficiency under visible-light illumination by extending the light absorption range and promoting charge separation and electron transfer. 146 Last but not least, a new type of photoelectrochemical (PEC) system without an external bias has also been developed to simultaneously achieve the generation of H 2 O 2 and electricity in recent years.…”
Section: Metal-free Graphitic Carbon Nitridementioning
confidence: 99%
“…In addition to all of the abovementioned catalysts, PCNs were also used to produce H 2 O 2 from mixtures of water and alcohols (Table ). More specifically, PCNs in conjunction with transition-metal catalysts, nitrogen vacancies, mesoporous morphologies, oxygen enrichment, or alkali metal dopants, have shown excellent reactivity. Notwithstanding all of these excellent photocatalysts, a high-power light source (at least >150 W) was essential to achieve high reactivity, and a higher production rate of the generated H 2 O 2 was only possible with at least 250 W light power (very expensive lamps). From all of these data, it is clear that a robust catalyst is essential to reduce cost and increase production.…”
Section: Introductionmentioning
confidence: 99%